Lifestyle behaviors, obesity, and perceived health among men with and without a diagnosis of prostate cancer: A population-based, cross-sectional study - Markwell Stephen J; Paragi-Gururaja Rammarayan; Courneya Kerry S; Rogers Laura Q; Imeokparia Remi (BMC, 2008)
Abstract Background A better understanding of how prostate cancer survivors differ from men without prostate cancer and whether these potential differences vary across demographic subgroups will help to focus and prioritize future public health interventions for improving the health and well-being of prostate cancer survivors. Therefore, our study aims were to compare lifestyle behaviors, body mass index (BMI), and perceived health in men with and without a diagnosis of prostate cancer in a national, population-based sample and to explore whether these comparisons differ for demographic subgroups. Methods In a cross-sectional study, men aged ≥ 40 were identified from the Behavioral Risk Factor Surveillance System (BRFSS) 2002 data (n = 63,662). Respondents reporting history of prostate cancer (n = 2,524) were compared with non prostate cancer controls (n = 61,138) with regard to daily fruit and vegetable servings (FVPD), smoking, alcohol, sedentary behavior, BMI, and perceived health. Multivariable logistic regression calculated adjusted odds ratios (OR) and 95% confidence intervals (CI) for the entire sample and for age, race, education, and urbanicity subgroups. Results Men with prostate cancer did not differ from men without prostate cancer with regard to smoking, alcohol, sedentary behavior, and obesity but were more likely to consume ≥ 5 FVPD (OR, 95% CI: 1.30, 1.09-1.56) and report poor or fair health (OR, 95% CI: 1.62, 1.33-1.97). Subgroup analyses demonstrated attenuation of the higher likelihood of ≥ 5 FVPD among prostate cancer survivors in rural respondents (OR, 95% CI: 0.98, 0.72-1.33). Poorer perceived health was greatest if ≤ 65 years of age (OR, 95% CI: 2.54, 1.79-3.60) and nonsignificant if black (OR, 95% CI: 1.41, 0.70-2.82). Smoking and alcohol which were not significant for the sample as a whole, demonstrated significant associations in certain subgroups. Conclusion Although efforts to enhance perceived health and healthy lifestyle behaviors among prostate cancer survivors are warranted, demographic subgroups such as prostate cancer survivors ≤ 65 and rural populations may require more aggressive interventions.